Modifications to Electronic Nicotine Delivery Systems: Content Analysis of YouTube Videos - Massey, Zachary B; Li, Yachao; Holli, Jessica; Churchill, Victoria; Yang, Bo; Henderson, Katherine; Ashley, David L; Huang, Jidong; Popova, Lucy (JMIR Publications, 2020)
BackgroundAs user modification can alter the addictiveness and toxicity of electronic nicotine delivery systems (ENDS), more research is needed to understand the types, motivations, risks, and information sources that lead to these product alterations. YouTube has been identified as a major platform where ENDS users obtain and share information about ENDS products and modifications. However, a comprehensive study of ENDS modification videos on YouTube is lacking. ObjectiveThis study aimed to analyze the content of YouTube videos depicting modifications of ENDS. MethodsYouTube was searched in March 2019 to identify videos depicting ENDS modifications. Search terms were derived from interviews with ENDS users and current literature. We used 28 search phrases that combined the words vape and vaping with modification-related key terms (eg, custom build, modification, and dripping). The final sample included 168 videos. ResultsVideos were 1 to 108 min long (median 9.55). Presenters were largely male (117/168, 69.6%), white (94/168, 56.0%), and older than 25 years (94/168, 56.0%). Most videos gave how to instructions (148/168, 88.1%), but few offered warnings (30/168, 17.9%) or mentioned commercial alternatives to modifications they presented (16/168, 9.5%). The ENDS devices most often featured were drippers (63/168, 37.5%) and refillable tanks (37/168, 22.0%). The most often modified ENDS components were coils (82/168, 48.8%) and e-liquids (34/168, 20.2%), which included adding other substances, such as cannabis, to the e-liquids (6/168, 3.6%). Most videos portrayed ENDS modifications positively (106/168, 63.1% positive; 60/168, 35.7% neutral; and 2/168, 1.2% negative) and were either neutral or positive in their overall portrayal of ENDS devices (78/168, 46.4% positive; 89/168, 53.0% neutral; and 1/168, 0.6% negative). ConclusionsThis study identified several concerning trends in popular YouTube videos on ENDS modifications, including lack of warnings, the addition of marijuana derivatives to e-liquids, and the positive portrayal of ENDS devices and modifications. By identifying the types of modifications (coil and e-liquid being the most prevalent), this study sets an agenda for research on the effects of modifications.